Additive manufacturing of an iron-based bulk metallic glass larger than the critical casting thickness. (June 2018) - Mahbooba, Zaynab; Thorsson, Lena; Unosson, Mattias; Skoglund, Peter; West, Harvey; Horn, Timothy; Rock, Christopher; Vogli, Evelina; Harrysson, Ola
Graphical abstract: Abstract: Fe-based bulk metallic glasses (BMG) are of increasing research interest, driven in part by a unique combination of mechanical, magnetic and chemical properties. However, the maximum thickness and geometry of BMGs achievable in traditional manufacturing processes is limited. This work examines the capabilities of laser based powder bed additive manufacturing (AM) to produce relatively large Fe-based bulk metallic glass specimens. AM fabricated specimens exceed the critical casting thickness of the material by a factor of 15 or more in all dimensions. Resulting microstructural and mechanical properties are reported. Despite decreasing quench effect with increasing build thickness, X-ray diffraction analysis suggests that a fully amorphous structure was maintained throughout the build. However, a low concentration of sparsely distributed nano-grain clusters was discovered using a high-resolution electron backscatter diffraction scan. The results pave the way for novel applications of metallic glasses achievable through appropriate material design and optimization of existing additive manufacturing processes.